Pengaruh Orientasi Kewirausahaan, Digital Marketing Capability, dan Akses Permodalan Fintech terhadap Kinerja UMKM Kuliner di Kabupaten Sumbawa - Nabila Alifya Safitri; Fahlia Fahlia (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to analyse the influence of Entrepreneurial Orientation, Digital Marketing Capability, and Access to Fintech Capital (Peer-to-Peer Lending) on the Performance of Culinary MSMEs in Sumbawa Regency. The novelty of this study lies in integrating entrepreneurial posture, digital marketing capability, and fintech-based capital access into a single causal model for culinary MSMEs operating in a non-metropolitan area. Previous studies have commonly examined these factors separately or within large urban business contexts, whereas this study positions digital marketing capability and fintech access as complementary strategic resources that can strengthen MSME performance under local market constraints. A quantitative survey was conducted with 100 owners or managers of culinary MSMEs registered on online food-ordering platforms and having accessed fintech P2P Lending services. Data were analysed using multiple linear regression with classical assumption tests. The results show that Entrepreneurial Orientation, Digital Marketing Capability, and Fintech Capital Access have positive and significant effects, both partially and simultaneously, on MSME performance measured through sales growth and profitability. Entrepreneurial Orientation provides the strongest standardized contribution, followed by Digital Marketing Capability and Fintech Capital Access. Theoretically, this study contributes to MSME performance literature by demonstrating that business performance in non-metropolitan digital transition contexts is shaped by the strategic combination of entrepreneurial behaviour, market-facing digital capability, and finance-enabling fintech access. Practically, the findings imply that culinary MSME development in Sumbawa requires integrated strengthening of entrepreneurial competence, digital marketing skills, and responsible access to alternative financing.